Outcomes of Children Who Present to the Emergency Department After Hematopoietic Cell Transplantation. Issue 12 (25th December 2021) - Bergmann, Kelly R.; Orchard, Paul J.; Roback, Mark G.; Gaillard, Philippe; Furnival, Ronald A.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Our primary objective was to describe emergency department (ED) presentation, treatment, and outcomes for children after hematopoietic cell transplantation (HCT). Our secondary objective was to identify factors associated with serious infection in this population. Methods: This is a retrospective review of HCT patients who presented to our university children's hospital ED from January 1, 2011, to June 30, 2013. Emergency department presentation, treatment, and outcomes were described. Descriptive statistics were used to compare children with definite serious infection with those without serious infection. Multiple binary logistic regression was performed for risk factors associated with definite serious infection. Results: Fifty-four HCT patients (132 encounters) presented to our ED. Most were transplanted for a malignant (46%) or metabolic (36%) diagnosis and were recipients of bone marrow (51%) or umbilical cord blood (45%). Fever was the most common complaint (25%). Emergency department laboratory (64%) or imaging (58%) studies were frequently obtained. Admission was common (n = 70/132, 53%), with 79% (n = 55) of admissions to intensive care or bone marrow transplant units. Thirty-five encounters had definite serious infection, 5 had probable serious infection, and 92 had no serious infection. Fever ( P < 0.001) and high-risk white blood cell (WBC) count of less than 5 or greater than 15 k/μL ( P < 0.001) were associated with definite serious infection. Fever (odds ratio = 8.84, 95% confidence interval = 2.92–26.73) and high-risk WBC (odds ratio = 6.67, 95% confidence interval = 2.24–19.89) remained significantly associated with definite serious infection in our regression model. Conclusions: Children presenting to the ED after HCT require extensive support and resources, with more than half requiring admission. Fever and high-risk WBC are associated with serious infection.